Penerapan Strategi Pembelajaran Studi Kasus untuk Meningkatkan Pemahaman Toleransi Beragama Siswa Kelas IX C SMP Islam Annur’ain - Dita Aulia Damayanti; Mustofa Mustofa; Aizana Nur A'ini; Yoga Dwi Wijanarko; Novia Ramadhani; Ardyna Ayu Mahardhien (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2025)
Religious tolerance is an essential value that must be strengthened in educational environments to foster mutual respect and harmonious social interaction among students. However, students’ understanding of religious tolerance concepts is often limited when learning activities rely solely on conventional teaching methods. This study aimed to analyze the implementation of the case study learning strategy in improving students’ understanding of religious tolerance material in Class IX C at SMP Islam Annur’ain. The research employed a qualitative descriptive approach conducted over three stages: planning, implementation, and evaluation. The participants consisted of 28 students of Class IX C. Data were collected through classroom observations, interviews, documentation, and learning outcome assessments. The findings showed that the application of the case study learning strategy significantly increased students’ comprehension of religious tolerance concepts, encouraged active participation, improved critical thinking skills, and fostered respectful attitudes toward differences in religious beliefs. Students demonstrated better abilities in analyzing social issues related to tolerance and proposing appropriate solutions within real-life contexts. The study implies that the case study learning strategy can serve as an effective and contextual approach in Islamic education learning, particularly in strengthening students’ social and moral values. Future studies are recommended to apply this strategy in broader educational settings and different learning subjects to examine its effectiveness more comprehensively.